Pelatihan Penguatan Karakter Siswa Melalui Program Kreatif-Edukatif Di SMPN 3 Slahung Ponorogo - Prayogo, Tonny Ilham; Utama, Arya Bakti; Mahira Ks, Muhammad Izza; Mafaza, Ibrahim Putra (STMIK Royal, 2025)
SMPN 3 Slahung Ponorogo has been facing major challenges in character implementation, especially regarding integrating moral values with interesting learning methods for students. The continuous loss of innovation in character learning approaches can lead to a lack of effectiveness in the formation of students' personalities to think logically, critically and innovatively. Therefore, the implementation of creative-educative programmes as an effort to strengthen students' character through innovative and enjoyable activities. This study aims to analyse the effectiveness of the creative-educative program in strengthening student character at SMPN 3 Slahung, Ponorogo. The research method employed is qualitative research with a post-positivism paradigm on students. The approach in this research employs an interpersonal approach to be able to meet face-to-face directly with students. Data collection techniques were carried out through observation, interviews and documentation to obtain an in-depth description of the implementation of the programme. The findings of this study show that the creative-educative program at SMPN 3 Slahung, Ponorogo is able to significantly improve students' discipline, responsibility and literacy attitude to be able to internalise moral values, especially in the fields of fiqh and tahfidz al-Qur'an. This confirms that the creative-educative approach can be an effective model for character learning in junior secondary schools. Keywords: character; creative-educative; educational technology; student training Abstrak: SMPN 3 Slahung Ponorogo menghadapi tantangan utama dalam penerapan karakter, terutama terkait mengintegrasikan nilai-nilai moral dengan metode pembelajaran yang menarik bagi siswa. Kurangnya inovasi dalam pendekatan pembelajaran karakter dapat menyebabkan kurangnya efektivitas dalam pembentukan kepribadian siswa untuk berpikir secara logis, kritis dan inovatif. Oleh karena itu, penerapan program kreatif-edukatif sebagai upaya untuk memperkuat karakter siswa melalui kegiatan yang inovatif dan menyenangkan. Penelitian ini bertujuan untuk menganalisis efektivitas program kreatif-edukatif dalam penguatan karakter siswa di SMPN 3 Slahung, Ponorogo. Metode penelitian yang digunakan adalah penelitian kualitatif dengan paradigma post-positivisme pada siswa. Adapun pendekatan pada penelitian ini menggunakan pendekatan interpersonal untuk dapat bertatap muka secara langsung bersama siswa. Teknik pengumpulan data dilakukan melalui observasi, wawancara dan dokumentasi guna memperoleh gambaran mendalam mengenai implementasi program tersebut. Hasil penelitian ini menunjukkan bahwa program kreatif-edukatif di SMPN 3 Slahung, Ponorogo mampu meningkatkan disiplin,tanggung jawab dan sikap berliterasi siswa secara signifikan untuk dapat menginternalisasi nilai-nilai moral khususnya bidang fiqh dan tahfidz al-Qur’an.Kata kunci: karakter; kreatif-edukatif; teknologi pendidikan; pelatihan siswa